The Spillover Effects of Russian Sanctions on CIS Economies - Kotlíková, Barbora; Zeynalov, Ayaz; Pantea, Smaranda; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis analyses the spillover effect of economic sanctions imposed on Russia in 2022 on the economic growth of the countries of Commonwealth of Independent States (CIS). The research aims to examine the impact of the sanctions on trade, remittances, and foreign direct investments, which are the three main linkages between Russia and other CIS members identified in previous research. The research questions include the effects of sanctions on the GDP growth in CIS countries, the impact of rubble depreciation on remittances flowing into CIS countries, and the potential benefits for Russian trading partners such as China, India, Turkey, and Saudi Arabia. The thesis uses a VAR model to estimate the response of the GDP of a selected economy to the change in the Russian GDP. The results shows that the GDPs of all selected countries move opposite the Russian GDP in the corresponding or the subsequent period, evaluating the sanctions' impact on the countries’ growth as not overall negative.
Vedoucí práce: Ayaz Zeynalov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses